The virtuous circle of corporate social responsibility and corporate financial performance: the mediating role of firm reputation / Vani Tanggamani, Azlan Amran and T. Ramayah - Tanggamani, Vani; Amran, Azlan; Ramayah, T. (Faculty of Accountancy, 2019)
Profitability is undeniably the main goal of business organizations. This study focuses on the effect of previous-year CSR practices to current-year financial performance, and then its effect on future-year CSR practices. This study also investigates the mediating effect of current-year firm reputation on the relationship between previous-year CSR practices and current-year financial performance, and on the relationship between current-year financial performance and future-year CRR practices. Using a stratified random sampling, 200 public listed firms on Bursa Malaysia were selected as sample of this study. Content analysis of their annual reports from year 2013 to 2015 and company website was carried out to determine their CSR practices disclosure, ROA and firm reputation. Partial least squares – structural equation modelling was used to analyse the samples. Findings showed that previous-year CSR practices lead to significant and positive effect on current-year reputation and corporate financial performance. Current-year reputation mediates the relationship between previous-year CSR and current-year corporate financial performance. However, current-year corporate financial performance does not lead to future-year CSR practices disclosure. This study showed that CSR practices have immediate positive effect on corporate financial performance but the profitability did not lead to more disclosure in subsequent-year CSR practices. Hence, further study might explore a wider time gap between current-year corporate financial performance and future CSR practices. Conclusively, CSR practices are critical success factor that must be effectively and efficiently implemented by firms